A Preliminary Study of Diastereoselectivity in the PdII‐Catalyzed C(sp3)‐H Alkoxylation of Cyclic Systems. Issue 10 (16th February 2016) - Yang, Xinglin; Sun, Tian‐Yu; Rao, Yu
Abstract: Primary mechanism of a Pd II ‐catalyzed 8‐aminoquinoline‐directed C−H alkoxylation was investigated. It was understood that the Pd II ‐catalyzed C(sp 3 )−O bond formation proceeded through a concerted reductive elimination from the Pd IV intermediate in the cyclic system. Deuteration experiments and related computational studies elucidate that intrinsic conformation determined the diastereoselectivity of the Pd II ‐catalyzed C−H alkoxylation of cyclic carboxylic acids. Abstract : All roads lead to Rome : Both cis and trans β‐C(sp 3 )‐H bonds of the cyclohexane carboxylic acid could be activated and alkoxylated with 8‐aminoquinoline as the directing group and Pd(OAc)2 as the catalyst. Both cis and trans mono‐methoxylated amides were transformed to cis / trans dimethoxylated products (see scheme). Deuteration experiments and related computational studies elucidate that the first introduced methoxyl group controlled the second alkoxylation reaction through a steric hindrance effect.